Rezension von: Althoff, Gerd, Die Ottonen - Lubich, Gerhard (Württembergisch Franken, 2001)
Gerd Althoff, Die Ottonen. Königsherrschaft ohne Staat (Urban-Taschenbücher, Bd. 473), Stuttgart/Berlin/Köln (Kohlhammer) 2000. 283 S.